Analysis of the challenges in implementing guidelines to prevent the spread of multidrug-resistant gram-negatives in Europe. Issue 5 (19th May 2019) - Tacconelli, Evelina; Buhl, Michael; Humphreys, Hilary; Malek, Veronika; Presterl, Elisabeth; Rodriguez-Baño, Jesús; Vos, Margreet C; Zingg, Walter; Mutters, Nico T
Abstract : Objective: The main objective of the study was to investigate major differences among European countries in implementing infection prevention and control (IPC) measures and reasons for reduced compliance. Design: An online survey including experts in IPC and a gap analysis were conducted to identify major limitations in implementing IPC guidelines. Setting: Europe. Main outcome measures: Four areas were targeted: (1) healthcare structure, (2) finances, (3) culture and (4) education and awareness. Perceived compliance to IPC measures was classified as low (<50%), medium (50% to 80%) and high (>80%). Countries were classified in three regions: North-Western Europe (NWE), Eastern Europe (EE) and Southern Europe (SE). Results: In total, 482 respondents from 34 out of 44 (77.3%) European countries participated. Respondents reported availability of national guidelines to control multidrug-resistant Gram-negatives (MDR-GN) in 20 countries (58.0%). According to participants, compliance with IPC measures ranged from 17.8% (screening at discharge) to 96.0% (contact precautions). Overall, three areas were identified as critical for the compliance rate: (1) number of infection control staff, (2) IPC dedicated educational programmes and (3) number of clinical staff. Analysis of reasons for low compliance showed high heterogeneity among countries: participants from NWE and SE deemed the lack of educational programmes as the most important, while those from EE considered structural reasons, such as insufficient single bed rooms or lacking materials for isolation, as main contributors to the low compliance. Conclusions: Although national guidelines to reduce the spread of MDR-GN are reported in the majority of the European countries, low compliance with IPC measures was commonly reported. Reasons for the low compliance are multifactorial and vary from region to region. Cross-country actions to reduce the spread of MDR-GN have to consider structural and cultural differences in countries. Locally calibrated interventions may be fruitful in the future.